Online booking versus travel agents: Perspective of young tourists in Serbia - Seočanac, Marijana; Kraguljac, Vladimir; Milašinović, Danko (Hotel and Tourism Management, 2019)
For several decades there has been a growing trend of a tourist getting informed about the destination and its aspects using the Internet and other media. Nowadays, this is increased to a higher level by the fact that, after initial search, more and more tourists start to arrange their trip, accommodation and additional services by themselves. These facts put a traditional travel agent in a very demanding position. Namely, he/she needs to be capable of performing all the activities in a much effective way, which would make them still competitive in the market. The main objective of this study is to investigate the behavior of contemporary young tourists in Serbia, in order to determine what aspects of business modern travel agents and online booking systems should improve to meet their needs. The results of this study could be used as a guideline by travel agents and designers of online services for their further development.